2016
DOI: 10.1589/jpts.28.2358
|View full text |Cite
|
Sign up to set email alerts
|

Impact of work environment and work-related stress on turnover intention in physical therapists

Abstract: [Purpose] This study was conducted to provide basic data for solutions to reduce the turnover rate of physical therapists. It should help create efficient personnel and organization management by exploring the impact of the work environment and work-related stress on turnover intention and analyzing the correlation between them. [Subjects and Methods] A survey was conducted with 236 physical therapists working at medical institutions in the Daejeon and Chungcheong areas. For the analysis on the collected data,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 11 publications
6
14
0
Order By: Relevance
“…The results of this study are relevant to the theory proposed by Fairbrother and Warn (2003) that the ability to manage physiological and psychological pressures has a significant impact on job satisfaction. Stress can make job dissatisfaction, increased turnover, and loss of labor (Samad, 2006) and the results of the study by Applebaum et al (2010) and Lee et al (2016), as described in previous studies above confirm this.…”
Section: 1work Environment and Stress Affects Job Satisfactionsupporting
confidence: 66%
See 1 more Smart Citation
“…The results of this study are relevant to the theory proposed by Fairbrother and Warn (2003) that the ability to manage physiological and psychological pressures has a significant impact on job satisfaction. Stress can make job dissatisfaction, increased turnover, and loss of labor (Samad, 2006) and the results of the study by Applebaum et al (2010) and Lee et al (2016), as described in previous studies above confirm this.…”
Section: 1work Environment and Stress Affects Job Satisfactionsupporting
confidence: 66%
“…The implication is that employees with higher work stress experience will experience low levels of job satisfaction and vice versa, resulting in turnover intention. Moreover, Lee et al (2016) suggest that it is necessary to make improvements to the work environment and reduce work stress so that it is expected to reduce employee turnover.…”
Section: 2research Objectivesmentioning
confidence: 99%
“…Next, job stress also found to have positive relationship with turnover intention. Multiple studies have confirmed their relationship (Lee, Seo, Lee, Lee, Jeon, & Han, 2016;Lo, Chien, Hwang, Huang, & Chiou, 2017). Job stress has become the common matter in banks.…”
Section: Discussionmentioning
confidence: 97%
“…According another study, result demonstrate that the employees' perseption of high commitment compensation reduce the likelihood of their turnover intention [9].. Almost all research on turnover intentions takes place in companies or institutions whose number of human resources has stopped working high [6], [7], [9]- [11]. This research is different from other studies.…”
Section: Introductionmentioning
confidence: 83%
“…Compensation and commitment variable have negative and significant effect of turnover intention [5]. According another study finding, based on statistically, there is significant negative correlation between turnover intention and work environment [6], [7].…”
Section: Introductionmentioning
confidence: 99%